Pengaruh Penggunaan Mobile Banking Terhadap Kepuasan Nasabah (Studi Kasus Mahasiswa UINSU) - Putri Wulandari; Nurkosrina Aisah; Chairina Chairina (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
Mobile banking or commonly called M-Banking is a banking service provided by banks to support the smoothness and ease of banking activities. This research uses quantitative research, because the focus of this research is to determine the effect of mobile banking on customer satisfaction. The purpose of this study was to determine the use of mobile banking on customer satisfaction. There are positive and negative impacts on the use of mobile banking. The positive impact that occurs is that customers can easily make any transactions, customers can also pay utility bills, water and so on with the features provided by mobile banking, while for the negative impacts of the existence of mobile banking such as smishing fraud, namely fraud that in the form of phishing where the fraudster will disguise himself as a bank to ask for data on a bank account, there is a risk of data theft by irresponsible parties.